Análise dialélica de populações de milho-pipoca para rendimento, capacidade de expansão e resistência à lagarta-do-cartucho - Peterlini, Edicarlos (2016)
With the main objective to evaluate the general combining ability (GCA),varietal effects and heterosis for grain yield, expansion capacity and resistance to fall armyworm, twelve populations of popcorn were crossed in a complete diallel scheme without reciprocals, totaling 66 hybrid combinations. These F1’s along with their parents and three checks were evaluated in field experiments carried out at two sites, Maringa / PR and Araruna / PR.These experiments were designed in a partial balanced square lattice design triple 9x9. The data were subjected to analysis of variance intrablocks with recovery of interblock information. The evaluated traits were: grain yield, number of ear rows, number of kernels per row, ear diameter, ear length, plant height, ear height, male tasseling, female silking, popping expansion and the degree of damage caused by the fall armyworm. Significant effects were observed for all variables. The adjusted means were employed to apply the Griffing’s (1956) method in order to estimate the GCA and the method of Gardner and Eberhart (1966) to estimate the varietal effects and heterosis. In the general, genotypes UNB 2U C5, PARA 172 e PR 023 showed great promise for improving grain yield, expansion capacity and resistance to fall armyworm simultaneously. Regarding grain yield were selected UNB 2U C5, PARA 172, BOYA 462 and PR 023 in Maringa, and ARMZ 13050, VIÇOSA, BOZM 260 e PR 023 in Araruna for intrapopulational improvement. The varieties ARMZ 07049, BOYA 462, PARA 172 and SAM 09/09 and the hybrids ARMZ 07049 x SE 013 and UNB 2U C5 x PR 023 may be suitable for reciprocal reccurent selection. For expansion capacity were indicated the genotypes UNB 2U C5 and SAM 09/09 to intrapopulational improvement. Varietal heterosis effect indicated PR 023, PA 091, ARMZ 13050, VIÇOSA, PARA 172 and UNB 2U C5 and specific heterosis indicated the combination SAM 09/09 x UNB 2U C5 to reciprocal reccurent selection. Diallel analysis showed possibilities for intrapopulational improvement to PARA 172, SE 013, PR 023 and PA 091 to inbred lines synthesis with fall armyworm resistance. Combinations PARA 172 x BOZM 260 and PA 091 x BOYA 462 may be indicated to improve using reciprocal reccurent selection.